Antifungal activity of chitosan against soil-borne plant pathogens in cucumber and a molecular docking study. Issue 1 (1st January 2021) - Onaran, Abdurrahman; Bayar, Yusuf; Karakurt, Tuncay; Tokatlı, Kader; Bayram, Mustafa; Yanar, Yusuf
Abstract : In this study, we investigated the antifungal activity of four different chitosan against Sclerotinia sclerotiorum and Fusarium oxysporum f.sp . cucumerinum (FOC). In addition, molecular docking studies of the chitosan compound against plant pathogens have been evaluated. Concentrations of 0.2, 0.3, 0.5, 1 and 2 mg/mL of each chitosan were used. The activity rate increased as the amount of concentration increased. Strong antifungal effects were observed at concentrations of 1 and 2 mg/mL of chitosan used against test fungi. For the first time with this study, the activity of chitosan against F. oxysporum f. sp. cucumerinum and molecular docking studies against both test pathogens were determined.